Developing software beyond customer needs and plans: an exploratory study of its forms and individual-level drivers. Issue 22 (17th November 2019) - Bianchi, Mattia; Marzi, Giacomo; Zollo, Lamberto; Patrucco, Andrea
Abstract : Excessive software development is the tendency to develop new software above and beyond the requirements of the market and/or planned specifications. It is a widespread phenomenon involving both risks and flexibility advantages. As it represents a challenging dilemma for software developers, it is important to study its human origins. Drawing on the tripartite model of individual attitudes, this study investigates the influence of developers's cognitive (intuitive and rational thinking styles), affective (emotional attachment) and behavioural (reliance on past experiences) traits on two forms of excess, beyond needs and beyond plans. Using survey data on 307 software developers, this study shows that different manifestations of excess are associated with distinct traits of software developers. Emotional attachment drives beyond needs excess. A positive (negative) association is found between relying on past experiences and beyond needs excess (beyond plans excess). An intuitive cognitive style fosters the inclusion of extra features in the new product scope, whereas a rational style might lead to developing one-size-fits-all software that targets the needs of a broad user base. These findings contribute to research on the development of digital new products and production technologies by offering a comprehensive yet fine-grained picture of excessive software development's nature and drivers.